PERFORMA SET NET BERDASARKAN PROFIL ARUS DI PERAIRAN TELUK MALLASORO JENEPONTO - Putra, Aswad Eka (FAPETKAN UNTAD, 2016)
Set net catch operated in Mallasoro Bay is very fluctuating. The fluctuations strongly assumed related to te current profile in that area. The objective of this study was to investigate the relationship between current profile with the set net catch. It was applied the linier regression for assessing its relationship. Data was collected for 35 days in set net fishing ground in Mallasoro Bay, Jeneponto. The results indicated that current direction and velocity play an important role in controlling set net productivity with significance value is 0,000028. By individually test shown that current velocity is the most influential that potentially reduces 7.29 units of set net catch.Keyword: set net, current, fish capture